Bridging Theory and Practice Through Real-World Language Assessment Design - Dewi, Desi Surlitasari; Manurung, Sulastri; Manuhutu, Natalia; Saputro, Isnaini Eddy; Widhiyanto, Widhiyanto; Wahyuni, Sri; Ardhi, Mega Aulia (Vision: Journal for Language and Foreign Language Learning, 2025)
Language assessment is a crucial component of effective language teaching. However, many pre-service teachers lack sufficient training in assessment practices, resulting in a gap between theoretical knowledge and practical application. This study explores how pre-service teachers perceive the effectiveness of a project-based approach to designing and administering real-world language assessments and examines the challenges they face. Combining a closed questionnaire and semi-structured interviews, the study gathers quantitative and qualitative data from twenty-five pre-service teachers. The findings revealed that hands-on involvement in assessment design enhances teachers' understanding of key assessment principles, increases confidence, and bridges the gap between theory and practice. However, participants also faced challenges, particularly in ensuring the validity and reliability of their assessments. These challenges were manageable with the support provided in the course, indicating the value of structured guidance and expert collaboration in developing assessment literacy. The findings underscore the value of integrating theory with practice in teacher training, providing important insights for language assessment education. Future research could examine larger samples, long-term impacts of such training, and the role of digital tools in developing assessment literacy.